Primary synovial sarcoma thyroid: an unusual presentation (Journal of Pathology of Nepal, 2020)
Primary Synovial sarcoma of the thyroid gland is a rare sarcoma. We report a case of synovial sarcoma of the thyroid gland in a 2-yr-old boy presenting with a palpable progressively increasing neck mass, high resolution ultrasound revealed a heterogeneous lesion measuring 5 x 4 cm identified in the right lobe compressing the left lobe. A total thyroidectomy was performed and grossly both the lobes were involved. Histologically, the tumor was a biphasic synovial sarcoma which was confirmed by immunohistochemical markers showing positive expression for vimentin, Epithelial membrane antigen &Transducin-like enhancer of split-1. This is an unusual location for the occurrence of primary synovial sarcoma and aggressive nature the early diagnosis is difficult, and no definite treatment regimens are being defined due to the rarity of neoplasm.